2014
DOI: 10.1111/1759-7714.12102
|View full text |Cite
|
Sign up to set email alerts
|

Tumor response and clinical toxicity associated with second‐line chemotherapy regimens for advanced non‐squamous non‐small cell lung cancer: A retrospective cohort study

Abstract: Background: Previously reported superior tumor response of pemetrexed in the second-line setting for advanced non-squamous non-small cell lung cancer (advNS-NSCLC) has never been confirmed in real-world studies. Platinum-based doublet is frequently used in the second-line setting for advanced NSCLC in China. Methods: A retrospective cohort study was conducted including patients receiving pemetrexed or docetaxel-based chemotherapy in the second-line setting for advNS-NSCLC in four Chinese tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The superior tumor response and better safety profile associated with pemetrexed treatments in the real-world first-line setting for AdvNS-NSCLC were consistent with what were observed in Chinese patients receiving pemetrexed treatment in the second-line setting. 18 Our study observed superior tumor response but highly comparable clinical toxicity associated with pemetrexed treatment when compared with docetaxel–platinum doublet. Because the highly comparable clinical toxicity between the two doublets should consume similar hospital resources for AE management, the observed superior tumor response associated with pemetrexed treatment was the only known factor contributing to the saved hospital costs for nonchemotherapy drugs and nondrug care associated with pemetrexed treatment.…”
Section: Discussionmentioning
confidence: 49%
“…The superior tumor response and better safety profile associated with pemetrexed treatments in the real-world first-line setting for AdvNS-NSCLC were consistent with what were observed in Chinese patients receiving pemetrexed treatment in the second-line setting. 18 Our study observed superior tumor response but highly comparable clinical toxicity associated with pemetrexed treatment when compared with docetaxel–platinum doublet. Because the highly comparable clinical toxicity between the two doublets should consume similar hospital resources for AE management, the observed superior tumor response associated with pemetrexed treatment was the only known factor contributing to the saved hospital costs for nonchemotherapy drugs and nondrug care associated with pemetrexed treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Third, almost all patients in our study cohort had adenocarcinoma lung cancer, which has lower expression of thymidylate synthase, a proven predictor for better response to pemetrexed treatment [ 27 ]. Finally, Chinese ethnicity in our study cohort could be another potential predictor to pemetrexed treatment as our previous study [ 11 ] also found much stronger response associated with pemetrexed treatment in the second-line setting in Chinese patients when compared to other studies mainly including Caucasian patients. Thus, the observed superior clinical effectiveness associated with pemetrexed treatment in our study should be further evaluated for their potential impact on overall survival in Chinese patients using a better study design and the possible predictive roles of age, platinum agent, thymidylate synthase, and Chinese ethnicity for the treatment response to pemetrexed in the first-line setting for advNS-NSCLC should be further investigated to guide future clinical practices.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, to our knowledge, pemetrexed has never been compared with other third-generation cytotoxic agents for clinical effectiveness and clinical toxicity in the first-line setting for advNS-NSCLC in Chinese patients. Thus, we conducted this retrospective cohort study to assess clinical effectiveness and clinical toxicity associated with platinum-based doublets in the first-line setting for advNS-NSCLC to confirm previously reported data demonstrating significantly improved tumor response associated with pemetrexed treatment in the second-line setting [ 11 ] and to provide general additional clinic evidence to support treatment decision making in the first-line setting for advNS-NSCLC.…”
Section: Introductionmentioning
confidence: 93%